THE DEVELOPMENT OF STUDENTS’ INTRAPERSONAL INSTRUMENT OF ELECTRICAL ENGINEERING PROGRAM VOCATIONAL SCHOOLS IN BALI - I Gede Ratnaya; Gaguk Margono (JISAE: Journal of Indonesian Student Assessment and Evaluation, 2017)
This research aimed to develop an instrument to measure the intrapersonal students’ of skill Electrical Engineering Program at Vocational High School in Bali by using Likert scale. This capability is important in regulating and monitoring personal’s goals during vocational education at SMK. This instrument has been tested to 110 students at Engineering Utilization of Electricity Program in the entire province of Bali. The validation of the instrument through the content validation by the experts, the validation grains measure with Momment Product engineering, and the validation of the construct done by factor analysis. Factor analysis uses the confirmation method Maximum Likelihood (ML) with the conformity or suitability obtained Chi Square amounted to 113,8 (p-value = 0,2622) and Goodness of Fit Index (GFI) by 0.92.